The Specifics of Religious Issues in Ukrainian Gender Electronic Mass Media - Karpovets, Maksym; Petrushkevych, Maria; Shershnova, Olena (Journal of Education Culture and Society, 2022)
Aim. The purpose of this study was to analyze religious issues in gender and feminist electronic mass media in Ukraine, taking into account the specifics of their policy, audience, and communication strategy Methodology. The empirical methods were gathered by a grouping of sites and electronic media: the official sites, the convergent scanned print media, and the social network Facebook. Overall, the 21 electronic mass media were analyzed. The main method of this research is a discourse analysis of religious topics. The main identified topics are representation of religions, political issues, gender history of religion, female priesthood, dogma of religion, pedagogical and scientific topics, critique of religion/church, anti-gender and religion, LGBT issues, sexuality, body, and religion. Only a small amount of material and topics are dedicated to religion, which is marginalized in the Ukrainian media. Conclusions. Our main conclusion is that the more analytical analysis in the material, the more tolerant the authors are to religion, but not to religious organizations. The sensitive topics of sexual orientation, sexual violence, pedophilia, and abortion rights related to church activities, are raised in the feminist/gender mass media. Originality. The coverage of religious issues depends on the type of media that presents a particular gender discourse: the more radical Ukrainian media in their visions, the less critical and stereotypical the representation of religion. Most Ukrainian gender media reflect general trends in the representation of religion.